Nové trendy při prepúšťaní zamestnancov - Grenčíková, Adriana; Španková, Jana (Univerzita Pardubice, 2011)
Outplacement, as a voluntary form of consultancy to employee after sacking, is also applied and provided by companies in our conditions. This support increases the chance of being employed again, the opportunity of obtaining a view of options in the labour market, information and skills. Of course, it also needed to entertain advantages and disadvantages by an employer, especially those ones of economic nature. On the other hand, it is also a kind of image shaping.
Keywords: outplacement; personnel work; human resources; redundancy; strategic planning